Republic of Madagascar : Fourth Review Under the Extended Credit Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2019)
Madagascar's economic recovery continued in 2018, notwithstanding challenges related to the presidential election in November/December 2018. While some economic pressures developed in the second half of 2018, economic conditions remained generally positive. Completion of the presidential election, continued implementation of the economic reform program, and stable functioning of public institutions have buttressed confidence, and the newly-elected President has committed to pursuing the country's reform program, including plans to address some slippages.